Words and Deeds in Renaissance Rome : Trials before the Papal Magistrates - Cohen, Thomas V. (Thomas Vance), 1942- (Book collections on Project MUSE., 1993)
The social historian, searching for the basis of a culture, often turns to a study of ordinary people. Perhaps one of the most revealing places to find them is in a court of law. In this presentatoin of nine criminal trials of sixteenth-century Rome (1540-75), where magistrates kept verbatim records, Thomas and Elizabeth Cohen paint a lively portrait of a society, one that is reminiscent of Boccaccio. These stories, however, are true. Each trial transcript is followed by an essay that interprets the beliefs, codes, everyday speech, and personal transactions of a world that is radically different from our own. The people on trial include assassins, a spell-caster, an exorcist, an adulterous wife, several courtesans, and the peasant cast of a bawdy, sacrilegious play. Out of their often pognant troubles, and their machinations, comes a vivid revelation of not only the tumultuous street life of Rome but also rituals of honour, the power and weakness of women, and the realities of social and economic hierarchies. Like cinema-verite, Words and Deeds in Renaissance Rome gives us an intimate glimpse of a people and their world.